A High-Performance Li-Mn-O Li-rich Cathode Material with Rhombohedral Symmetry via Intralayer Li/Mn Disordering - Song, Jin (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.